High Rates of Return to Soccer After Primary Hip Arthroscopic Labral Repair for Femoroacetabular Impingement Syndrome - Akeem Henry; Louis Kang; John‐Rudolph Smith; Malik Dancy; Gavin Ward; Bruce A. Levy; Mario Hevesi; Aaron J. Krych; Kelechi R. Okoroha (Arthroscopy, Sports Medicine, and Rehabilitation, 2026)
Purpose To evaluate return‐to‐sport (RTS) outcomes and patient‐reported outcomes in soccer players after primary hip arthroscopic labral repair for femoroacetabular impingement syndrome. Methods All patients undergoing primary hip arthroscopy with labral repair for femoroacetabular impingement syndrome from 2011 to 2022 were retrospectively reviewed. Patients who had a minimum 2‐year follow‐up, played soccer, and had no prior hip surgery were included. Patient‐reported outcome measures and RTS were collected at the final follow‐up. Logistic regression was used to assess associations between potential covariates (e.g., age, sex, and level of play) and RTS. Results Forty‐eight hips in 41 patients (21 men [51%]) with a mean age at surgery of 21.9 years (range 13‐41 years) were included. Thirty‐two out of the 41 patients (78%) played at either the recreational or high school level. After removing those who did not return for nonmedical reasons, 29 out of 36 (81%) patients were able to return to soccer. Among patients with available patient‐reported outcome measures, significantly greater postoperative scores were seen in the RTS group for Hip Outcome Score‐Activities of Daily Living (95 vs 85) and Hip Outcome Score‐Sport (88 vs 71, both P < .05). Soccer players younger than 25 years had significantly higher odds of RTS compared with those aged 25 years or older (odds ratio = 8.8, P = .006). Five hips (10%) underwent revision at the final follow‐up. Conclusions Soccer players undergoing primary hip arthroscopic labral repair for femoroacetabular impingement syndrome reported an 81% RTS rate at a minimum 2‐year follow‐up, with most returning at the same or higher level of play. At a mean follow‐up of 5.5 years, most patients achieved Patient Acceptable Symptom State thresholds. Younger age was associated with a higher likelihood of return to sport. Level of Evidence Level IV, therapeutic retrospective case series.